Cellular connectomes as arbiters of local circuit models in the cerebral cortex - Emmanuel Klinger (Nature Portfolio, 2021)
Large-scale connectomes from the mammalian brain are becoming available, but it remains unclear how informative these are for the distinction of circuit models. Here, the authors use connectome statistics to test competing models of local cortical circuits with approximate Bayesian computation.